Cardamom Aromatherapy for Nausea and Vomiting of Pregnancy in the First Trimester: A Structured Literature Review - Aura, Annisa; Sri Purwanti, Anik (KHD Production, 2026)
Nausea and vomiting of pregnancy (NVP), commonly referred to as emesis gravidarum in early pregnancy, is highly prevalent and may impair nutrition, hydration, daily functioning, and quality of life. Pharmacological treatment is available, but many pregnant women prefer low-risk complementary approaches when symptoms are mild to moderate. Cardamom (Elettaria cardamomum) aromatherapy has been proposed as a practical non-pharmacological option, yet the evidence base remains scattered and methodologically uneven. Objective: This structured literature review synthesized DOI-traceable evidence on cardamom aromatherapy and related complementary aromatherapy approaches for NVP in first-trimester pregnancy. A PRISMA-informed search was conducted across PubMed/MEDLINE, ScienceDirect, Scopus, Web of Science, Cochrane Library, and Google Scholar. Only peer-reviewed sources with active DOI links were retained. Evidence was grouped into direct cardamom evidence, pregnancy aromatherapy evidence, NVP guidelines and measurement literature, and cardamom pharmacology or safety evidence. Direct evidence specific to cardamom in first-trimester NVP was limited, but one pregnancy-focused cardamom essential oil study and one cardamom inhalation trial in cesarean-related nausea support biological plausibility and potential antiemetic effects. Broader aromatherapy trials using lemon, peppermint, or mint reported reductions in nausea severity. At the same time, guidelines and systematic reviews recommend cautious use of complementary approaches as adjuncts rather than replacements for standard care. Cardamom aromatherapy is a promising supportive intervention for mild-to-moderate emesis gravidarum, but current evidence is insufficient to support a strong clinical recommendation. Larger randomized controlled trials using validated tools such as PUQE-24, careful safety monitoring, placebo control, and standardized essential oil protocols are needed.